Strategi Blue Bird dalam Menghadapi Disrupsi Ride-Hailing di Indonesia - Adinda Nabila Fajar; Erwin Permana; Muhammad Rubiul Yatim (Jurnal Ekonomi dan Pembangunan Indonesia, 2025)
The development of the digital ecosystem has disrupted the transportation sector. Traditional transportation businesses have shifted to online transportation. This study aims to analyze Blue Bird's strategy in facing the ride-hailing disruption in Indonesia. The research was conducted using a descriptive qualitative approach. The data was sourced from digital searches and observations. The results show that the digital transformation implemented by PT Blue Bird Tbk has improved operational efficiency and competitiveness in the highly competitive transportation market. The My Blue Bird application, with real-time tracking and cashless payment features, has streamlined the booking process and strengthened customer loyalty. The data indicates an increase in app usage and a reduction in operational costs, supporting the effectiveness of the company's digital strategy. Strategic collaboration with ride-hailing platforms has also significantly contributed to market expansion and increased fleet occupancy. The success of this strategy is reflected in the rise in booking volume and overall customer satisfaction. As a further step that has not been fully implemented, it is recommended that Blue Bird explore the application of AI-based predictive models to optimize fleet scheduling and route dynamics. The use of this technology can provide more accurate demand forecasts and support strategic decision-making in resource allocation. Additionally, the development of a customer feedback system integrated with digital analytics will allow the company to respond to consumer trends and preferences more effectively. These measures, supported by enhanced digital infrastructure and cross-sector collaboration, are expected to further boost Blue Bird's efficiency and growth in the digital disruption era.